2004
DOI: 10.1177/112067210401400310
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thrombocytosis in Diagnosis of Giant Cell Arteritis and Differentiation of arteritic from Non-Arteritic Anterior Ischemic Optic Neuropathy

Abstract: Patients with GCA had significantly (p <0.0001) higher values of platelet count, ESR, CRP and WBC but lower values for hemoglobin and hematocrit compared to the NA-AION group. Predictive ability of an elevated platelet count did not surpass elevated ESR or CRP as a diagnostic marker for GCA. Thrombocytosis may complement ESR. Hemoglobin, hematocrit and WBC were much less predictive of GCA. Elevated CRP had a greater predictive ability for GCA compared to ESR or the other hematologic parameters; thrombocytosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 33 publications
4
38
1
Order By: Relevance
“…Costello et al [12] compared laboratory markers in 121 patients with biopsy-proven GCA to 287 patients with nonarteritic anterior ischemic optic neuropathy. They found that whereas an elevated CRP was the best isolated predictor of GCA, followed by elevated ESR, there was an improvement in the prediction of GCA if platelets and ESR were both elevated.…”
Section: Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costello et al [12] compared laboratory markers in 121 patients with biopsy-proven GCA to 287 patients with nonarteritic anterior ischemic optic neuropathy. They found that whereas an elevated CRP was the best isolated predictor of GCA, followed by elevated ESR, there was an improvement in the prediction of GCA if platelets and ESR were both elevated.…”
Section: Plateletsmentioning
confidence: 99%
“…They found no improvement in prediction of GCA with elevated platelets alone, or in combination with elevated CRP. Elevated platelet count was defined as greater than 400 Â 10 3 [12]. Foroozan et al [13] looked at a population of 91 patients suspected of having GCA, and compared ESR and platelet counts in the biopsy-positive (47 patients) versus biopsy-negative (44 patients) groups.…”
Section: Plateletsmentioning
confidence: 99%
“…Some reported that elevated CRP level was an independent risk factor for age-related macular degeneration 34,35 as well as an indicator of its progression, 36 although others failed to support these findings. 37,38 Elevated CRP was also found to correlate positively with a diagnosis of arteritic anterior ischaemic optic neuropathy 39,40 and with vascular conditions such as retinal vein occlusion 41,42 and normal-tension glaucoma. 43 However, the value of CRP in patients with RAO has not yet been examined.…”
Section: Introductionmentioning
confidence: 97%
“…Some authors have reported an association between thrombocytosis and vision loss in GCA, possibly from an increased risk of thrombosis[16, Class IV]. Other authors have found no significant difference in the incidence of severe ischemic events associated with thrombocytosis[15, Class III]. & Three retrospective studies have evaluated the use of aspirin as an adjuvant therapy to steroids in GCA.…”
mentioning
confidence: 97%
“…[14,15, Class III], the effect of thrombocytosis on vascular occlusion remains unclear. Some authors have reported an association between thrombocytosis and vision loss in GCA, possibly from an increased risk of thrombosis[16, Class IV].…”
mentioning
confidence: 99%